Aplikasi Mobile Pendeteksi Gangguan Mental Mahasiswa dengan Menggunakan Metode Forward Chaining - Arunseto Pambudi; Siti Aminah; Bagus Kristomoyo Kristanto (Prosiding SISFOTEK, 2021)
Mobile device technology (mobile) is one of the most widely used communication and information devices in March 2020 as many as 55.43% of mobile device users and the number of mobile device users will continue to rise leaving the desktop over time. Mental disorders in modern times are increasingly becoming a serious problem in society. Most of the incidents of suicide are related to mental-emotional disorders. Decision Support System (DSS) or Decision Support System (DSS) is a system capable of providing problem solving capabilities. Forward chaining is a method of DSS that uses an inference engine and can be described logically as an iterative application of the modus ponens. The purpose of this study is to build a student mental disorder detector mobile application using the forward chaining method. This research discusses from system design, application implementation to application testing. The results of this study are a trial result and an informative mobile application and of course able to detect mental disorders of students.